Challenges and alternatives towards peacebuilding: A rural development perspective (2020)
Rural development and peacebuilding in Colombia have been highly prioritized by higher education institutions since the signing of the Peace Agreement between the National Government and the FARC-EP. This has resulted in the need to further analyze rural strategies that contribute towards a better life for the population of territories where armed conflict is coming to an end, whilst understanding the pressing uncertainty that this process implies; on the one hand, for the urgency of generating rapid and concrete responses to social justice and equity, and on the other, because fulfilling the agreement guarantees scenarios of non-repetition of the war in the country.These were some of the reflections that motivated the research project “Rural development alternatives for peacebuilding: educational strategies to strengthen the ability of producers and young people that contribute to the coffee production chain in the municipalities of Leiva, Policarpa and Los Andes of the department of Nariño, with international impact in the province of Carchi-Ecuador”. This work is presented as an investigative result that contains the analysis of theoretical and territorial dynamic contributions regarding the construction of peace, education and the economy for rural development.